Menangani gerakan Islam Liberal di Indonesia: Kajian tentang usaha Dewan Dakwah Islamiyah Indonesia (DDII) dan halangannya / Darwin Zainuddin - Darwin , Zainuddin (2017)

(untitled)
Islamic Dakwah Council of Indonesia was established on 26 February 1967. In Jakarta, it is religious organization which put dakwah (evangelical) as the main activity. Dakwah means here not only to deliver Islamic mission in verbal (tabligh), but also to take the comprehensive way (syumuliah), including to dakwah bil hal (behavior manner), bil kitabah (writing), and social engagement through many sectors such as education, empowerment the function of mosque, training the da’i (Islamic missionary), etc. The research which will be discussed by the researcher in this thesis can give an explicit meaning according to the aim of investigation then the researcher emphasizes the objectives of investigation consist : Investigating at the liberalisation movement in Indonesia, discussing at Islamic organization steps to deal the Islamic liberalisation in Indonesia, recognizing the Islamic Dakwah Council of Indonesia, categorizing the effort which was conducted by Islamic Dakwah Council in handling the Islamic liberalisation movement in Indonesia, and classifying the obstacle which is confronted by Islamic Dakwah Council in handling the Islamic liberalisation movement in Indonesia. The researcher chose qualitative research method to produce the descriptive data which aims to describe a phenomenon or situation which happened at researching. It will give attention to comprehend at recognizing the Islamic Dakwah Council of Indonesia within conducting Islamic dakwah. This research is emphasized to Islamic Council efforts and obstacles in order to handle the Islamic liberalization movement in Indonesia within dakwah bi al-lisan, dakwah bi al-hal, and dakwah bi al-kitabah. Due to explain this research methodology, the researcher analyzes ; in research invention, in research scope, data collection method, and analyzing data. In order to do observation the researcher used some methods to receive the data consists ; interview, investigation and documentation. The interview result of research is the main data for the researcher in this research. As for the research result which was received from documentation and investigation is only as additional and data support to explain the research result.